Meat production of young and adult Kejobong goats fed diets with different protein concentration - Nuning Ari Purnami; Endang Purbowati; Edy Rianto (Faculty of Animal Science, Universitas Brawijaya, 2021)
This study was aimed to examine the effect of dietary crude protein (CP) concentration on carcass and meat production in young and adult Kejobong goats. This study used 8 young (5 months) and 8 adult (9 months) Kejobong goats; which were allocated to a randomized nested design, with an age of goat as the nest, and treatment applied was dietary protein concentration (T1: 9.96%; T2: 14.66%). The parameters observed were dry matter intake (DMI), CP intake (CPI), body weight gain (BWG), and the production of carcass meat. The results showed that the DMI of adult goats (910 g/d) was higher (P<0.05) than that of young goats (680 g/d). The goats fed diet T2 had higher (P<0.05) DMI, CPI, and BWG (855 g, 140 g, and 94 g/d, respectively) than those of T1 (725 g/d, 80 g/d, and 59 g/d). Slaughter weight, carcass weight and carcass meat weight, and carcass meat percentage of adult goats (28.09 kg, 13.19 kg, 8.60 kg and 64.94%, respectively) were higher (P <0.05) than those of young goats (20.06 kg, 8.72 kg, 5.46 kg, and 62.06%, respectively). The weight and percentage of carcass meat of T2 (8.30 kg and 64.99%, respectively) were higher (P<0.05) than those of T1 (5.75 kg and 62.06%, respectively). The meat-bone ratio of adult goats was higher (P<0.05) than that of young goats (3.53 vs 2.85). The meat-bone ratio of T2 (3.58) was higher (P<0.05) than that of T1 (2.80). It was concluded that adult Kejobong goats produced more meat than the young ones, and the goat-fed diet with 14.66% CP produced more meat than that with 9.96% CP.